Rural–urban disparities in hospitalisation for myocardial infarction in systemic lupus erythematosus in the USA - Jasvinder A Singh; Sumanth Chandrupatla (Lupus Science and Medicine)
Objective To assess whether rural–urban disparities exist in people with SLE for hospitalisation with myocardial infarction (MI).Methods We used the 2016–2019 US National Inpatient Sample data that contain all hospitalisation data. In people with a diagnosis of SLE, we assessed the multivariable adjusted ORs (aORs) to examine the association of rural patient residence with MI hospitalisation, while adjusting for demographics, payer, income, hospital characteristics and the Deyo-Charlson Comorbidity Index.Results We found that the crude rates of patients hospitalised with MI per 100 000 area specific SLE hospitalisations were higher in rural versus urban residents with SLE, 2265 versus 1435 (p value<0.001). In the multivariable-adjusted model that accounted for demographics, insurance payer, household income, comorbidities and hospital characteristics including geographical location, we found that rural residence was associated with an aOR of 1.98 (95% CI, 1.71 to 2.29; reference category, urban residence) of MI hospitalisations in people with SLE. Other factors significantly associated with the risk of MI were male sex, Medicaid or private insurance, urban not teaching or urban teaching hospital, Midwest region and a private hospital control, either for profit or not for profit.Conclusion Rural residence doubled the risk of MI hospitalisation in people with SLE independent of demographics, payer status, social determinants of health and hospital characteristics. Our study highlights the disproportionate effect of rurality on health outcomes in people with SLE within the USA and a clear rural–urban gap disparity. Interventions to reduce this disparity are needed.